Choice overload reduces neural signatures of choice set value in dorsal striatum and anterior cingulate cortex. (December 2018) - Reutskaja, Elena; Lindner, Axel; Nagel, Rosemarie; Andersen, Richard; Camerer, Colin
Abstract Modern societies offer a large variety of choices1, 2, which is generally thought to be valuable3–7 . But having too much choice can be detrimental1–3, 8–11 if the costs of choice outweigh its benefits due to 'choice overload'12–14 . Current explanatory models of choice overload mainly derive from behavioural studies13, 14 . A neuroscientific investigation could further inform these models by revealing the covert mental processes during decision-making. We explored choice overload using functional magnetic resonance imaging while subjects were either choosing from varying-sized choice sets or were browsing them. When choosing from sets of 6, 12 or 24 items, functional magnetic resonance imaging activity in the striatum and anterior cingulate cortex resembled an inverted U-shaped function of choice set size. Activity was highest for 12-item sets, which were perceived as having 'the right amount' of options and was lower for 6-item and 24-item sets, which were perceived as 'too small' and 'too large', respectively. Enhancing choice set value by adding a dominant option led to an overall increase of activity. When subjects were browsing, the decision costs were diminished and the inverted U-shaped activity patterns vanished. Activity in the striatum and anterior cingulate reflects choice set value and can serve as neural indicator of choice overload. Having too many choices can lead to choice overload. Reutskaja et al. find that brain activity in striatum and anterior cingulate reflects subjects' engagement in decision making as a function of choice set size and can serve as an indicator of choice overload.